Performance analysis of field oriented controlled PMSM based electric truck - Achary, Sanskruti; Chaudhari, Rutul; Chauhan, Siddharthsingh K. (Institute of Advanced Engineering and Science, 2024)
The electric vehicle (EV) concept is considered the ideal solution to save the environment from pollution occurring due to internal combustion engines or ICE-based vehicles. However, electric power trains have found more penetration in the segment of passenger vehicles and electric buses. This paper presents the performance of an electric truck. Field-oriented controlled permanent magnet synchronous motor (PMSM) is used for the powertrain of the proposed electric truck. The performance of the proposed electric truck is analyzed for propulsion as well as regenerative mode of operation using MATLAB. The effect of different gradient conditions of the road surface on the behavior of the proposed truck is observed. The presented simulation results depict the satisfactory operation of the proposed PMSM-driven electric truck for various operating conditions.